Solidarity economy organizations as a mechanism for the integration of small and medium cassava producers in Yopal, Casanare (Colombia) - Cárdenas Mora, Sandra Milena; Manzanares Mendoza, Kelly Johanna (Cooperativismo & Desarrollo, 2017)
Purpose: The purpose of this paper is to propose economic and social alternatives for the management of small and medium cassava producers in Yopal, Casanare (Colombia), based on the constitution of organizations grounded on the principles of solidarity economy. Description: Throughout the paper, the economic importance of cassava in the region is acknowledged, and the value chain of cassava is exposed. Point of view: The associative solidary systems are analyzed as a form of organization, as well as the possibilities offered by these as business mechanisms to stimulate the production and commercialization of cassava in Yopal, Casanare. Conclusions: Solidarity organizations constitute a viable mechanism to unite efforts and obtain important collective benefits in the context of Yopal’s cassava producers, which is why these organizations form the basis of the present reflection, taking into account the economic potential of cassava in this population.